Stabilization of novel immunoglobulin switch regions G-quadruplexes by naphthalene and quinoline-based ligands. Issue 9 (3rd March 2016) - Carvalho, Josué; Ferreira, João; Pereira, P.; Coutinho, E.; Guédin, Aurore; Nottelet, Pierre; Salgado, Gilmar F.; Mergny, Jean-Louis; Queiroz, J.A.; Sousa, F.; Cabrita, Eurico J.; Cruz, C.
Abstract: The topological study of novel quadruplex-forming DNA sequences found in immunoglobulin switch regions Sμ and Sγ3 is described along with the synthesis and characterization of naphthalene and quinoline-based ligands for the G-quadruplex binding and stabilization. Several biophysical and biochemical techniques are employed to assess the G-quadruplex formation and stabilization by the ligands. The results indicate that 58Sγ3 folds into a parallel-stranded G-quadruplex structure in K + buffer while 33Sμ folds into a hybrid-type G-quadruplex in the same buffer. The novel naphthalene and quinoline-based ligands bind and stabilize specifically a variety of G-quadruplexes. This study provides evidence of the importance of G-quadruplex structures to the biology of immunoglobulin class switch recombination. Graphical abstract: